PENGARUH ARTIS K-POP SEBAGAI BRAND AMBASSADOR MAKANAN RINGAN TERHADAP PERSEPSI MEREK DAN MINAT BELI KONSUMEN - Novanda Dwi Ramadhani; Donny Dwi Setiabudi; Diva Apriliana Puspasari (Cahaya Ilmu Bangsa, 2024)
The Korean Wave phenomenon, including K-Pop, has become a strong trend among Indonesian people, especially the younger generation. This study aims to analyze the influence of K-Pop artists as snack brand ambassadors on brand perception and consumer purchasing interest in Indonesia. The use of K-Pop artists as brand ambassadors is increasingly popular, including in promoting snack products, which aims to improve brand image and encourage consumer purchasing decisions. This study uses a quantitative approach with a survey method through a Google Form-based questionnaire using a 5-point Likert scale. The research respondents were consumers who knew or had seen K-Pop artists as brand ambassadors for certain snack products. In addition, secondary data were obtained from journals, research reports, and other relevant sources. The results of the study indicate that K-Pop artists as brand ambassadors have a positive influence on consumer brand perception and purchasing interest. Good brand perception, supported by consumption experience and emotional associations, has also been shown to contribute significantly to consumer purchasing interest. This study underlines the importance of selecting brand ambassadors that are relevant to the target market to support the success of marketing strategies. This study is expected to contribute to companies in designing effective marketing strategies using K-Pop artists.